A study of patterns of adverse drug reactions in a tertiary care hospital of Andhra Pradesh, India - Vinutha, Sondi; Kamala, Kuna; Suresh, Nethala (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pharmacovigilance Programme of India (PVPI) is a step towards participation in WHO programme for International Drug Safety Monitoring. Pharmacovigilance (PV) system is an integral part of drug therapy, which helps in detection, monitoring and designing strategies to minimize the occurrence of Adverse Drug Reaction (ADRs). The present study is done to study the patterns of ADRs in a tertiary care government hospital. Methods: A total of 327 suspected ADR reports submitted to the pharmacovigilance unit at department of pharmacology under PVPI were evaluated for a period of two years with respect to age, sex, causative drug, organ system involvement and seriousness of ADRs. The causality assessment was done using WHO assessment method. Results: Female patients experienced more (54.13%) ADRs. The highest percentage (49.24%) of ADRs were seen in age group of 18-44 years, followed by 45-60 years (33.33%). Medicine department reported the maximum number (42.20%) of ADRs. Antimicrobial agents (27.83%) were the commonest group of drugs causing ADRs, followed by anti psychotics (15.90%) and analgesic drugs (10.70%). Skin is the major organ system affected (30.28%). Causality assessment revealed (51.99%) of the ADRs were possible. Majority of the ADRs (79.82%) were nonserious and (20.18%) were serious requiring hospitalization. Death occurred in five patients. Conclusions: The results suggest that there is under reporting and there is a need to create awareness among health care professionals(HCP) about the importance of Pharmacovigilance .The data also helps in designing strategies for framing policies towards safer use of drugs in future.